Distress Tolerance and Psychopathological Symptoms and Disorders: A Review of the Empirical Literature among Adults - Leyro, Teresa M. (2010)
In the present paper, we review theory and empirical study of distress tolerance, an emerging risk factor candidate for various forms of psychopathology. Despite the long-standing interest in, and promise of work on, distress tolerance for understanding adult psychopathology, there has not been a comprehensive review of the extant empirical literature focused on the construct. As a result, a comprehensive synthesis of theoretical and empirical scholarship on distress tolerance including integration of extant research on the relations between distress tolerance and psychopathology is lacking. Inspection of the scientific literature indicates that there are a number of promising ways to conceptualize and measure distress tolerance, as well as documented relations between distress tolerance factor(s) and psychopathological symptoms and disorders. Although promising, there also is notable conceptual and operational heterogeneity across the distress tolerance literature(s). Moreoever, a number of basic questions remain unanswered regarding the associations between distress tolerance and other risk and protective factors and processes, as well as its putative role(s) in vulnerability for, and resilience to, psychopathology. Thus, the current paper provides a comprehensive review of past and contemporary theory and research and proposes key areas for future empirical study of this construct.